1998
DOI: 10.1606/1044-3894.702
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Religion in Advancing a Culturally Sensitive Approach towards Child Maltreatment

Abstract: Religion is a dimension that can have a significant effect on child-rearing beliefs and parenting behaviors, and consequently on parents' approach toward child maltreatment. This potential effect can be explained by Kohn's (1963) hypothesis about the relationship between values, a significant component of religion, and child-rearing practices. This subject has been examined in a study that was the first of its kind on ultra-orthodox Jewish families in Israel. The findings provide preliminary knowledge on the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…The study, too, revealed that the religious participants regarded such issues more harshly than did their secular counterparts. Similarly Shor (1998) reported a relationship between religious affiliation and an orientation that supports obedience and harsh forms of punishment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study, too, revealed that the religious participants regarded such issues more harshly than did their secular counterparts. Similarly Shor (1998) reported a relationship between religious affiliation and an orientation that supports obedience and harsh forms of punishment.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast in Nigeria, a country with extreme cultural, social, economic, religious and political diversity, perception and care of persons with disabilities have been influenced by cultural beliefs that attribute the cause of disability to curse from God; family sins; offenses against the Gods; witches or wizards, and an evil spirit (Obiakor 1998). Shor (1998) noted that one of the critical components of culture is religion, which can have a major influence on values, beliefs, and educational practices such as child rearing.…”
Section: Introductionmentioning
confidence: 99%
“…storytelling, dressing modestly etc.). Other research on religion and the family has found that religiosity in parents is linked to protective factors, which have positive influences on the family structure (Shor 1998). In an increasingly anti-Islamic setting, the role of religion and its intersection with race and ethnicity in early socialisation is important (Iqbal, 2014).…”
Section: Parenting and Identity In Second Generation Families: Explorinmentioning
confidence: 99%
“…This situation has led the ultraOrthodox community to develop an independent network of organizations that serve as a partial alternative to external welfare services (Shapiro, 1997). The ultra-Orthodox community strictly upholds lofty religious and moral laws regarding the family and perceives child abuse as being morally forbidden by the Halakhah (Jewish law), but it is not perceived in terms of criminal behavior (Goldstein & Laor, 2007;Shor, 1998). Therefore, external intervention is perceived as a threat to the community, which places obstacles in the way of the child welfare service intervention, preferring to deal with the situation from within the community.…”
Section: The Ultra-orthodox Community In Israelmentioning
confidence: 99%
“…The literature asserts that particular sensitivity is needed with child welfare interventions in immigrant communities or communities with a specific culture or religion (e.g., Giovannoni & Becerra, 1979;Korbin, 1991;Malley-Morrison & Hines, 2004;Schmid & Benbenishty, 2011;Shor, 1998). However, the literature on intervention by child welfare services in closed religious communities is scarce.…”
mentioning
confidence: 99%